'Doing gender' in the wild berry industry: Transforming the role of Thai women in rural Sweden 1980–2012. Issue 2 (May 2016) - Hedberg, Charlotta
'Doing gender' has often been used as the theoretical entrance for research on gender issues in the social sciences. However, research has been accused of using the concept in a 'ceremonial' way, treating gendered structures as static. In response to this claim, this article investigates the process of 'hierarchization', or how gendered and racial hierarchies occur through everyday practices and political and economic contexts in the rural, wild berry industry in contemporary Sweden. The industry has gone through a thorough transformation, from irregular and small-scale production to regularized and large-scale production, which has affected the intersection of gender and racial structures. In particular, Thai women have gone from being active participants both as entrepreneurs and as workers, to working under native men, or being passive receivers of men's remittances. The mechanisms behind the intersection of gender and racial structures are a complex interplay of economic, social and institutional factors, which act on nested global, national and translocal scales.